IDC : prioritising development impact - Oji, Chijioke; Mokoaleli-Mokoteli, Thabang ([London] : SAGE, 2016)
Under the leadership of Geoffrey Qhena, the Industrial Development Corporation (IDC) made performance returns which were generally considered to be impressive. However, for Qhena himself, this was not enough. Qhena wanted more, intending to grow the development impact of the IDC by increasing its minimum loans from R1 million to R5 million in 2013. He wondered how best to achieve this in the current environment of economic uncertainty, and this text outlines the strategies deployed by Qhena in order to maintain IDC's progression.
Originally Published in: Oji, C., & Mokoaleli-Mokoteli, T. (2012). IDC: Prioritising Development Impact. WBS-2012-10. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Industrial Development Corporation of South Africa; Corporations -- Finance -- Case studies